Microstructure study on Al-Si bar produced by the new near shape casting technique - Prayitno, Dody; Hamzah, Esah; Mohd. Ghazali, Mohd. Zulkifli (1999)
In order to reduce cost of producing metal ingot, namely aluminium from its molten state, a new near shape casting equipment has been designed and fabricated. In this new technique molten metal was poured from a moving tundish into a copper mould that can be tilted until 6 degree. The cooled water spray was introduced at the bottom of the mould in order to cool the solidified metal. The as-cast bar was observed under optical microscope and hardness value taken. The results show that increasing tundish speed and reducing mould temperature reduces the dendritic grain size. Thus the mechanical property, namely hardness, increases